Преступление и наказание в рассказе Улика Алексея Скалдина - Okroj, Kinga (Studia Rossica Posnaniensia, 2024)
The article is devoted to the discussion of structural elements and motifs in the short story of the Russian modernist Aleksey Skaldin entitled Trace. In his work, the writer reinterprets certain aspects from Fyodor Dostoevsky’s novel Crime and punishment. It can be assumed that the two texts chosen for comparative analysis are marked by similar ideas (crime, punishment, Übermensch). The goal of the analysis is to underscore the shared and relevant contents of both literary works. The main character of Skaldin’s Trace, Ivan Vyakhirev, is guided by the theory of the division of society into outstanding and ordinary individuals, similarly to Rodion Raskolnikov. Vyakhirev can be seen as a variant of Raskolnikov. Even though he does not know the book Crime and punishment, he “develops” Raskolnikov’s theory. Vyakhirev wants to prove his own uniqueness, the final test being the murder of his old friend. Similar experiences and reasoning of the characters lead them, however, in completely opposite directions. Raskolnikov reevaluates his life and the views he held as he admits that he is not an outstanding individual above the law. Skaldin’s Trace illustrates the reverse path of human personality development. Initiatory signs appear on Vyakhirev’s path, but he is unable to see and use them, and he does not develop self-awareness. He rejects their power, embarking on a dark path. The interpretation of Skaldin’s text through the prism of the ideas contained in Crime and punishment leads to an in-depth reading of the meanings and symbols hidden in Trace (including guilt, freedom, and the female figure).